Ethics and law in biological research - Mazzoni, Cosimo Marco (Nijhoff law specials ;, 2002)
"This is a collection of essays reflecting a considerable range of different cultural experiences and different ethical underpinnings. The main subject is cloning. Cloning is the most accessible and most readily perceived point of convergence from which ethical judgements on the current developments of scientific investigations can be proposed. Cloning is also the "paradox" on which the confrontation between scientific research and popular imagination is focused."--Jacket